2010
DOI: 10.1007/s10608-009-9293-3
|View full text |Cite
|
Sign up to set email alerts
|

Anger, Aggression, and Irrational Beliefs in Adolescents

Abstract: This study examined whether a combination of anger, hostility, and irrational beliefs, i.e., intolerance of rules frustration, intolerance of work frustration, demands for fairness, and self-downing would predict physical, verbal, and indirect aggression and peer ratings of aggression. Follow-up analysis tested gender as a moderator of the relations between irrational beliefs and aggression, and anger and aggression. One hundred thirty-five high school-aged adolescents completed measures of irrational beliefs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 49 publications
(53 reference statements)
4
39
0
2
Order By: Relevance
“…Recent studies indicate that females are not less likely to experience feelings of anger than males. While some studies have found no or little gender differences [11,13,14], quite a few studies have suggested that feelings of anger are more frequent, more common and even more enduring among females than among males [10,[15][16][17][18]. for example, a recent study showed that adolescent girls had higher scores of self-assessed anger, anxiety and depression as measured by Becks youth Inventory [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that females are not less likely to experience feelings of anger than males. While some studies have found no or little gender differences [11,13,14], quite a few studies have suggested that feelings of anger are more frequent, more common and even more enduring among females than among males [10,[15][16][17][18]. for example, a recent study showed that adolescent girls had higher scores of self-assessed anger, anxiety and depression as measured by Becks youth Inventory [17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an angry emotional response may increase aggressive behaviors, while feelings of embarrassment or upset might actually be associated with lower levels of aggression. The positive association between anger and aggression has been widely supported [e.g., Arsenion et al, 2000; Baker and Bramston, 1997; Cornell et al, 1999; Deater-Deckard et al, 2010; Eisenberg et al, 2009; Fives et al, 2011; Lemery et al, 2002; Murray-Close et al, 2010; Peled and Moretti, 2007, 2010; Sprague et al, 2011]; however, only a handful of studies have examined the role of sadness in aggression and findings from these studies are mixed. While there is evidence that sadness is inversely related to aggression [Peled and Moretti, 2007, 2010; Zeman et al, 2002], other studies have found a positive relationship between sadness and externalizing behavioral problems [Eisenberg et al, 2002, 2009; Lemery et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of attitudes toward street violence demonstrated that acceptance of street-related violence was higher for males than for females (Taylor et al, 2010), and Buss and Perry (1992) found that men scored more highly on their physical aggression, verbal aggression, and hostility scales. However, Fives, Kong, Fuller, and DiGiuseppe (2011), using the Buss and Perry Aggression Questionnaire, found sex differences only for physical aggression, with males scoring more highly. With regard to year in school, no difference in attitudes toward violence has been found across Years 8 to 12 and Years 4 to 6 (Funk et al, 1999(Funk et al, , 2003.…”
Section: Group Differences: Sex and Year In Schoolmentioning
confidence: 90%